Diversity and otherness: transcultural insights into norms, practices, negotiations - Gaupp, Lisa; Pelillo-Hestermeyer, Giulia; Ciaudo, Joseph; Cismondi, Fabio; Espahangizi, Kijan; Hirschauer, Stefan; Marten-Finnis, Susanne; Niccolai, Marta; Reichardt, Dagmar; Höhne, Marek Sancho; Ursula Oettl, Barbara (De Gruyter Open Poland, 2021)
Frontmatter -- Contents -- List of Contributing Authors -- Acknowledgements -- 1 Re-thinking Diversity and Transculturality: Introduction -- 2 Epistemologies of Diversity and Otherness -- 3 Un/Doing Differences. The Contingency of Social Affiliations -- 4 The “Cultural Turn” of Postmigrant Conviviality. A Historical Case Study on Practices and Discourses of (Multi)Cultural Diversity in Switzerland, 1970s–1990s -- 5 Promoting a Hygienic Dress That Transcends Cultural Life-Worlds: Some Remarks on the Rejection of Western Clothes by a Chinese Minister to the United States in the Early Twentieth Century -- 6 Spaces of Otherness and Desire. Ballets Russes—Artist-Animators—Ethnographic Enquiry -- 7 ORLAN’s Hybridizations: From Virtual to Literal Cyborg // From Mortal to Immortal Being -- 8 Transculturally Speaking: Linguistic Diversity, Otherness and the Transformation of Public Spheres -- 9 Style, Sense and Senses: The Iconic and Transcultural Language of Italian Fashion -- 10 Encounters with Alterity: Romani on the Contemporary Italian Stage -- 11 Negotiating Gender in Germany—Normalizing Trans*Imaginations. On Aspects of Belonging to and Resisting the Normative Binary Gender Order -- 12 How to Curate Diversity and Otherness in Global Performance Art -- 13 Diversity in Scientific Communities: The Case of European-Japanese Cooperation at Fusion for Energy -- 14 Decolonizing Otherness Through a Transcultural Lens: Conclusion -- Academic Biographies -- List of Figures -- Index